Development of strategies to improve care for all in the communities served by a mid-size nonprofit health system in the United States - Cichetti, Jodi R.; Voight, Stephanie; Jansen, Jenna; Seim, Michael B. (Frontiers in Public Health, 2025)
WellSpan Health is a nonprofit integrated healthcare system serving 12 counties in south-central Pennsylvania and northern Maryland, a region marked by wide disparities in the demographic, social, and economic conditions of its people. Consequently, it is also marked by wide disparities in health status and health outcomes, including life expectancy. Beginning in the mid-1990s, WellSpan’s community health needs assessments identified numerous potential drivers of health disparities, and in recent years the hospital system has conducted increasingly sophisticated community health improvement plans to address disparities in ways compatible with the hospital system’s resources, capabilities, mission, and priorities. Because there is limited published information about how nonprofit health systems are implementing and evaluating community health improvement plans, we have documented key aspects of WellSpan’s progress including guiding principles and strategies, how pilot projects were identified and conducted, how community partnerships were developed and leveraged, and how data sources were used to guide decisions. WellSpan’s efforts have culminated in the recent adoption of a 30-year plan to improve overall life expectancy and quality of life and reduce disparities in these outcomes in the region served. The purpose of this paper is to share experiences and lessons learned during the multi-year effort leading to the development of this 30-year plan.